Inhibitory effect of recombinant TGF alpha-PE40 on vascular smooth muscle cell proliferation. - Wang Bing; Guan Zhan-jun; Zhang Guo-yuan; Wu Zong-gui; Xu Yong-hua; Jiang Wan-li; Rui Yao-cheng; Chu Zhi-yong (Acta Pharmacologica Sinica, 2016)
AIM: To study inhibitory effect of recombinant transforming growth factor alpha-Pseudomonas exotoxin fusion protein (TP40) on proliferation of the cultured vascular smooth muscle cells (SMC). METHODS: Expression of epidermal growth factor receptor (EGFR) mRNA and EGFR in cultured proliferating and quiescent SMC was analyzed with Northern blot and immunohistochemistry. Inhibitory effects of TP40 on SMC proliferation and protein synthesis were analyzed with crystal violet staining and [3H]leucine incorporation. Competition assays were performed by the addition of 100-fold excess of EGF. RESULTS: Expression of EGFR mRNA and EGFR in rapidly proliferating SMC increased than that in quiescent SMC. When the concentration of TP40 was 10 or 100 micrograms.L-1, inhibitory effects of TP40 on rapidly proliferating SMC proliferation and protein synthesis were much higher than that on quiescent SMC (P < 0.01), and the IC50 of [3H]leucine incorporation against rapidly proliferating and quiescent SMC were 8.01 (5.05-12.69) and 121.95 (90.98-163.47) micrograms.L-1. Excess EGF completely blocked inhibitory effects of TP40. CONCLUSION: The rapidly proliferating SMC express EGFR at a high level. TP40 selectively inhibited the proliferation of rapidly proliferating SMC. The cytotoxic effects of TP40 were specifically mediated by EGFR.